DESIGN AND DEVELOPMENT OF "BOLLYWOOD-ISASI HOLLYWOOD FILM" PARODI VIDEO USING R&D (RESEARCH AND DEVELOPMENT) - Jimmy Pratama; Alex Sandro (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
The very rapid development of technology in today's virtual world provides a separate space for creative people to produce copyrighted works in various expressions, including parody video works. The development of the virtual world is getting easier, and the development of platforms in cyberspace such as Youtube, Instagram, Facebook and so on can make someone easily share their experiences or stories on these platforms, one can also take advantage of these media to be used as a means of showing his creations which are the result of his personal creative thinking so that it can be enjoyed by the general public. Design and development of parody bollywood videos - Hollywood films using the R&D (Research and Development) research method used to develop parody videos to produce parody works that can be seen by the general public. These process steps are usually called the R&D cycle whose field is testing a work or product that will be used, in the R&D method before developing a product we must test the work or product that will be used in the end and revise it to correct deficiencies found in this stage. propose a research test that is used to develop parody videos to produce a parody work that can be seen by the general public.